Mixing Up the Mediterranean Model: Architecture Amid Urban Flux. (6th September 2017) - Molinari, Luca
Abstract : The Radical movement born in 1960s Italy sparked a rethinking of the urban landscape. Its key proponents, such as Andrea Branzi, understand the city as a constantly fluctuating organism, rather than an ever‐expanding Modernist assembly of parts with fixed functions. Luca Molinari – Professor of History and Theory of Contemporary Architecture at the Università degli Studi della Campania 'Luigi Vanvitelli', Naples – reflects on how this organic model recalls that of traditional Mediterranean towns. He traces the spread of its influence around the world in recent decades, and asks whether it could be a solution to the decline of suburbia in economically advanced nations.